Mangrove Kaboa (Aegiceras corniculatum): The Correlation Study of Indigenous People’s Knowledge to Ethnoconservation at Sancang Garut Beach - Rina Maryani; Diana Hernawati; Rinaldi Rizal Putra (Journal of Tropical Ethnobiology, 2023)
Kaboa (Aegiceras corniculatum) is a type of mangrove known as a typical plant in the Sancang Beach area because of its legends and myths. Currently, the number of Kaboa plants on Sancang Beach is decreasing. One of the causes can occur due to human interference, disturbances to the habitat or exploitation of these plants. The reduction of such species can be avoided by knowing the extent of people's knowledge of the Kaboa plant (Aegiceras corniculatum) and the ethnoconservation attitudes carried out. This study used quantitative methods with a correlational approach. It was conducted in Sancang Village, Sagara Village, Karyasari Village, and Karyamukti Village, Garut Regency with a research instrument in the form of a questionnaire given to 100 respondents from the four villages. The results showed that local people's knowledge of Kaboa plants was in the good category with an average value of 77.48/100 while the ethnoconservation attitude of the community towards Kaboa plants was in the partial category with an average value of 82.13. The value of the relationship between local community knowledge and ethnoconservation attitudes towards the Kaboa plant is 0.620, which indicates that there is a strong and unidirectional significant relationship between indigenous people's knowledge about the Kaboa plant (Aegiceras corniculatum) and the ethnoconservation attitude carried out. The level of indigenous knowledge that is considered good and the indigenous conservation attitude of the people who are in the category of favoring the Kaboa plant must be maintained and even increased so as to provide opportunities to maintain and preserve the Kaboa plant in its habitat